Las ONG microfinancieras peruanas: ¿siguen manteniendo su misión social? - Raquel Marbán Flores (AECOOP Escuela de Estudios Cooperativos, 2016)
In recent years, the growth of the microfinance sector has been significant. Either as a cause or as a consequence, some governments have decided to make it part of the financial system adapting regulatory frameworks to allow the sector to continue to expand as the number of formal institutions increases. It is the case in Peru where many NGOs have decided not to become regulated, arguing that this change could leave them to move away from the social aims for which they were created. In an increasingly competitive marketplace, where the legal framework encourages the regulation of microfinance institutions, there appears to be a need to study the potential future role of NGOs in the sector. In consideration of this question, this paper attempts to analyse the social role of those NGOs that have decided not to become regulated institutions. In this study a number of social indicators are analysed; these include the number of female clients, average loan amount and how loans are used, among others. These indicators will be used to attempt to evaluate the social role of unregulated NGOs and their prospects in this new context.